HUMAN CAPITAL AS THE BASIS OF EFFECTIVE PERFOMANCE OF ORGANIZATIONS - G. V. Goliguzova (Дискурс)
This article presents some aspects of the concept of "human capital". The authors outline approaches to defining this economic category and consider the possibility of including the concept of "human capital" in the conceptual economic category of synergetic effect of collaboration. The effective use of human capital provides an increase in productivity, and, therefore, contributes to economic growth of the organization, improves its efficiency and provides additional income. The features of the assessment of this economic category are also addressed.